2006
DOI: 10.1002/cphc.200600115
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Characterization of the Gas‐Phase O3⋅⋅⋅HO Hydrogen‐Bonded Complex

Abstract: We report a theoretical study on two gas-phase hydrogen-bonded complexes formed between ozone and hydroxyl radical that have relevance to atmospheric chemistry. This study was carried out by using CASSCF, CASPT2, QCISD, and CCSD(T) theoretical approaches in conjunction with the 6-311+G(2df,2p) and aug-cc-pVTZ basis sets. Both complexes have a planar structure and differ from each other in the orientation of the electronic density of the unpaired electron associated with the HO radical moiety. Our calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The same kind of calculation has been already performed on the pre-reactive hydrogen-bonded complex (C1). [20] Along the reaction path, we found the possible existence of the HO 4 polyoxide intermediate. This radical was first investigated at the CASSCF level of theory and in a further stage by performing a numerical optimisation [34,35] at the MRCI level of theory.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…The same kind of calculation has been already performed on the pre-reactive hydrogen-bonded complex (C1). [20] Along the reaction path, we found the possible existence of the HO 4 polyoxide intermediate. This radical was first investigated at the CASSCF level of theory and in a further stage by performing a numerical optimisation [34,35] at the MRCI level of theory.…”
Section: Methodsmentioning
confidence: 98%
“…We recently reported the pre-reactive O 3 ···HO hydrogenbonded complex, [20] and we refer the reader to that study for its discussion. In that work, we concluded that the best level of theory to describe this pre-reactive hydrogen-bonded complex is CCSD(T)//QCISD, because it can properly account for the dynamic correlation effects needed to describe the hydrogen-bond interaction, whereas the wavefunction is still reliable regarding its possible multireferential character.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 3 more Smart Citations